Key cardiopulmonary exercise testing indicators for predicting the risk of postoperative cardiopulmonary complications in patients undergoing thoracoscopic lung resection - Yang, Nan; Shi, Zhihua; Liu, Junfeng; Yuan, Yadong (Frontiers in Surgery, 2026)
ObjectiveTo explore the predictive value of key preoperative cardiopulmonary exercise testing (CPET) indicators for cardiopulmonary complications following thoracoscopic lung resection.MethodsPatients who underwent lung resection at the Department of Thoracic Surgery, Fourth Hospital of Hebei Medical University were selected. Information was collected for patients who completed CPET using the incremental exercise protocol. Hospitalization information, postoperative complications and follow-up data were analyzed. Correlations between postoperative cardiopulmonary complications and preoperative CPET indices were analyzed to identify threshold values.ResultsAmong 376 thoracoscopic lung resection patients, 52 experienced at least one complication (13.8%). Comparison between the cardiopulmonary complications group (CCP) and no complications group (NCCP) revealed significant differences in age, extent of lung resection, and lymph node metastasis (P < 0.05). Core CPET indicators including peak heart rate (peak HR), peak oxygen uptake (peak VO2), peak VO2%pred, peak metabolic equivalent (peak MET), and maximal workload %pred were significantly lower in the CCP group (P < 0.05). The sensitivity and specificity of peak VO2%pred <70%, peak MET <5, and maximal workload %pred <80% all exceeded 60%, with negative predictive values surpassing 90%. Positive predictive values of peak VO2 < 15 mL/(min·kg), peak VO2%pred <60%, peak MET <4, and maximal workload %pred < 60% exceeded 30%. Using these cutoff values resulted in high diagnostic accuracy with odds ratios of 6.2, 4.0, 4.6, and 3.2, respectively.ConclusionKey preoperative CPET indicators effectively evaluate postoperative complication risk in thoracoscopic lung resection patients. Peak VO2, peak VO2%pred, peak MET, and maximal workload %pred are associated with postoperative cardiopulmonary complications.